The Global Occurrences of Cleft Lip and Palate in Pediatric Patients and Their Association with Demographic Factors: A Narrative Review - Farah Asnely Putri; Madhuri Pattamatta; Sheylla Edu September Anita; Tantry Maulina (MDPI AG, 2024)
Objective: Orofacial clefts are one of the most common abnormalities that occur in the orofacial area. Due to their high prevalence, special attention provided to risk factors and their possible involvement in the occurrence of orofacial clefts is of importance. The objective of this study was to review the current global occurrence of orofacial clefts and the possible linkage of previously investigated risk factors to the occurrence of orofacial clefts. Review: The risk factors of orofacial clefts can be classified into two groups, modifiable risk factors and non-modifiable risk factors. Due to the extent of elaboration of each risk factor in each group, this current narrative review is limited to several mostly investigated risk factors, which included a review of parental age, sexual disparities, educational attainment, and income. Studies indicate that Asians are more likely than other races to have orofacial clefts, with a higher incidence rate in men than in women. There is evidence that the age of the parents is associated with the chance of the occurrence of orofacial cleft. The prevention of orofacial clefts and the distribution of medical resources depend heavily on a thorough understanding of epidemiology on a global scale. Nevertheless, the earlier studies concentrated on more developed nations or areas, and registry data from low-income nations had significant gaps. The findings of this narrative review can be used as the scientific basis for further research within this area. Conclusion: The occurrence rate of orofacial clefts remains high in several regions. Possible associations between parental age, sexual disparities, educational attainment, and family income to the occurrence of orofacial clefts remain contradictory, indicating the importance of further research to obtain more insights.